The Incidence and Risk Factors for Persistent Acute Kidney Injury Following Total Cavopulmonary Connection Surgery: A Single-Center Retrospective Analysis of 465 Children - Jia, Yuan; Luo, Qipeng; Su, Zhanhao; Xiong, Chao; Wang, Hongbai; Li, Yinan; Wu, Xie; Yuan, Su; Yan, Fuxia (Frontiers in Pediatrics, 2021)
Background: Acute kidney injury (AKI) after cardiac surgery contributes to adverse outcomes. We aimed to assess the incidence and identify the predictors for persistent AKI after total cavopulmonary connection (TCPC) surgery. Methods: A retrospective study, including 465 children undergoing TCPC surgery from 2010 to 2019, was conducted. We used pRIFLE criteria to define AKI and defined persistent AKI as AKIs occurring between postoperative day1 (POD1) and POD3 and sustaining at least on POD7. Univariate and multivariate logistic regressions were applied to analyze the predictors for persistent AKI. Results: A total of 35.3% patients developed AKI between POD1 to POD3 and 15.5% patents had persistent AKI after TCPC. Patients with persistent AKI had prolonged mechanical ventilation and ICU stay, and had higher rates of renal replacement treatment and reintubation, which was associated with higher hospitalization costs and in-hospital mortality. The independent predictors for persistent AKI were peripheral oxygen saturation (SpO2) upon admission, intraoperative fluid balance, POD0 maximal lactic acid, renal perfusion pressure (RPP), POD0 estimated glomerular filtration rate and POD0 total bilirubin. The areas under receiver operating characteristic curve (AUC) in the total cohort and the subgroup undergoing TCPC surgery after 2017 were 0.75 (95%CI, 0.66-0.82) and 0.87 (95%CI, 0.77-0.97), respectively. The acceptable AUCs (nearly 0.7) were achieved in other 5 subgroups and good calibration ability (p ≥ 0.05) were achieved in the total cohort and all six subgroups. Conclusions: Persistent AKI after TCPC was common and strongly associated with poorer in-hospital outcomes in Chinese pediatric patients. Six perioperative variables, including SpO2, intraoperative fluid balance, POD0 maximal lactic acid, RPP, POD0 moderate-to-severe kidney injury and POD0 total bilirubin, were identified as independent predictors for persistent AKI. Our findings may help to perform an early risk stratification for these vulnerable patients and improve their outcomes.